Bidirectional Recoil Leaders in Upward Lightning Flashes Observed at the Säntis Tower. Issue 18 (10th September 2021) - Sunjerga, Antonio; Rubinstein, Marcos; Azadifar, Mohammad; Mostajabi, Amirhossein; Rachidi, Farhad
Abstract: We report the observation of three negative upward flashes recorded by a high‐speed camera at the Säntis Tower during the Summer of 2019. The camera was operating at 10, 000 fps and an exposure time of 99 μs. Simultaneous measurements of the lightning current were obtained for all three flashes. The close electric field was measured for one of the observed flashes, which was analyzed in detail. In this flash, we observed 50 recoil leaders developing in the decayed channel with speeds characteristic of dart leader processes. Out of the 50 recoil leaders, 45 ended up as attempted leaders, three developed into M‐component‐type ICC (initial continuous current) processes, and two into return strokes. This study reveals that depending on the spatial and temporal properties of electric field in the area of the event and the main channel condition, recoil leaders can develop into different processes in upward negative lightning flashes such as attempted leaders, M‐components, M‐component‐type ICC events, mixed mode pulses, or return strokes. We observed M‐component‐type ICC events with junction heights as low as 137 m, while all of the observed mixed mode pulses seemed to attach directly to the structure. Bidirectional propagation of the recoil leader was also observed. Key Points: Recoil leaders main source of fast processes in negative lightning Recoil leaders initiate in bidirectional manner Mixed mode pulses connect directly to structure